Assessment of factors affecting flicker ERGs recorded with RETeval from data obtained from health checkup screening. - Taiga Inooka; Taro Kominami; Shunsuke Yasuda; Yoshito Koyanagi; Junya Ota; Satoshi Okado; Ryo Tomita; Yasuki Ito; Takeshi Iwase; Hiroko Terasaki; Koji M Nishiguchi; Shinji Ueno (PLoS ONE, 2023)
Purpose To determine the factors significantly associated with the amplitudes and implicit times of the flicker electroretinograms (ERGs) recorded with the RETeval system by analyzing the comprehensive data obtained during a health checkup screening. Methods Flicker ERGs were recorded with the RETeval system from 373 individuals who had a normal fundus and optical coherence tomography images. The sex, age, anthropometric, ophthalmologic, and hematologic data were collected from all participants who were 40- to 89-years-of-age. Univariable and multivariable linear mixed effects regression analyses were performed to identify factors that were significantly associated with the implicit times and amplitudes of the RETeval flicker ERGs. Results Univariable linear mixed effects regression analysis showed significant correlations between the implicit times and the best-corrected visual acuity, the age, the axial length, the blood sugar level, and the blood urea nitrogen level. Analyses by multivariable linear mixed effects regression identified that the axial length (β = 0.28), the age (β = 0.24), and the blood sugar level (β = 0.092) were three independent factors that were significantly correlated with the implicit times of the RETeval flicker ERGs. Univariable linear mixed effects regression analysis also showed significant correlations between the amplitudes of the RETeval flicker ERGs and the age, the platelet count, and the creatinine level. Multivariable linear mixed effects regression models identified the age (β = -0.092), the platelet count (β = 0.099), and the creatinine level (β = -0.12) as three independent factors that were significantly correlated with the amplitudes of the RETeval flicker ERGs. However, the smoking habits, body mass index, and the blood pressure were not significantly correlated with either the implicit times or amplitudes of the RETeval flicker ERGs. Conclusions Our results indicate that the age and some ophthalmologic and hematologic findings but not the anthropometric findings were significantly associated with the implicit times and amplitudes of the RETeval flicker ERGs. Thus, clinicians should remember these factors when analyzing the RETeval flicker ERGs.